AN ANALYSIS OF READING MATERIALS IN TEXTBOOK ENGLISH IN FOCUS FOR GRADE VII JUNIOR HIGH SCHOOL PUBLISHED BY DEPARTMENT OF NATIONAL EDUCATION (RETAIN, 2014)
AN ANALYSIS OF READING MATERIALS IN TEXTBOOK ENGLISH IN FOCUS FOR GRADE VII JUNIOR HIGH SCHOOL PUBLISHED BY DEPARTMENT OF NATIONAL EDUCATION Niken Wahyuningsih S1- English Education, Language and Art Faculty, Surabaya State University dan niken.agushari@gmail.com Drs. Aswandi, M.Pd S1- English Education, Language and Art Faculty, Surabaya State University Abstrak Tujuan penelitian ini adalah untuk mengetahui apakah materi reading dalam buku pelajaran English in Focus dapat memenuhi aspek isi, aspek penyajian, aspek penggunaan bahasa dan keterbacaan serta aspek hubungan antar bahan yang direkomendasikan oleh Pusat Perbukuan, Kementrian Pendidikan Nasional. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dimana hasil penelitian dideskripsikan dalam bentuk kata atau kalimat tanpa adanya perhitungan statistik. Hasil penelitian menunjukkan bahwa materi reading semester pertama pada buku pelajaran English in Focus tidak dapat memenuhi kriteria buku Bahasa Inggris yang berkualitas yang telah direkomendasikan oleh Pusat Perbukuan, Kementrian Pendidikan Nasional. Dari hasil penelitian ditemukan dua ketidaksesuaian di dalam buku pelajaran English in Focus sebagai berikut: (a) beberapa materi reading yang harus diajarkan di semester satu tidak dapat ditemukan dalam buku, dan (b) materi reading yang dapat mendorong pengembangan teknologi dan seni tidak ada dalam buku. Kata kunci: analisa, materi reading, buku pelajaran. Abstract The objectives of the study are to describe wehether the reading materials in English in Focus textbook for grade VII Junior High School can meet the aspect of contents, aspect of presentation, aspect of language use and readability and aspect of relation between chapters suggested by Pusat Perbukuan, Ministry of National Education. This study was designed as a documentary analysis in the form of descriptive qualitative research, in which the result would be described in the form of words without any statistical calculation. The result show that the reading materials of first semester in English in Focus textbook were not appropriate with the criteria of quality English textbook suggested by Pusat Perbukuan, Ministry of National Education. There were two non-conformities found in the textbook: (a) there were some reading materials which were not presented in the textbook and (b) there were no reading materials which could encourage the development of technology and arts. Keywords: analysis, reading material, textbook INTRODUCTION Nowadays English plays an important role in today’s global era. The importance of English cannot be denied since English is the most common language spoken everywhere. There are four skills that need to be learnt in learning English. They are listening, speaking, reading and writing. Those skills are used to create a discourse in daily life. According to Concord (1973) as cited in Nunan (2005:17) the relationship between those skills is very close in which the strength of each skill influence each other. Reading is one of the skills in English that has to be mastered by the students when they are learning English. Because of that, students have to learn reading as well as the other skills if they want to master English. According to Nunan (2003:68) reading is a fluent process where in building the meaning, readers should combine information from the text with their own background of knowledge. While, Alyousef (2005:144) states that “Reading can be seen as an “interactive” process between a reader and a text which lead to automaticity or (reading fluency)”. It is assumed that reading is not a passive skill because it needs so many times to practice and exercise. The improvement of the readers’ comprehension is based on how they work on it. It means that if the reader read more, they get better reading or comprehension. In teaching and learning process, teacher should considered the learning materials which are used in the class. Textbook is one of the learning materials which are commonly used. It is kind of printed materials which have an important part in teaching and learning process. According to Tomlinson (1999:2), textbook is a main learning material which is usually used by teacher and students. Textbook also has many advantages in teaching and learning process. According to Richard (2001:249), the advantages of textbook are (1) providing structure and a syllabus for a program; (2) helping standardized instruction; (3) maintaining quality; (4) providing a variety of learning resources; (5) being efficient; (6) providing effective language models and input; (7) training teachers; and (8) being visually appealing. To make students able to achieve the English materials, they need some English textbooks which have good quality. By learning those quality textbooks, they are able to improve their English skill productivity. Dealing with the quality of a textbook, in 2008 Department of National Education publishes some BSE (Buku Sekolah Elektronik) English textbooks. One of them is an English textbook for Seventh Graders of Junior High School entitled “English in Focus” which is not only used by public schools but also private schools. However, the researcher think there is no guarantee that textbook published by Department of National Education is meeting the expectation of quality English textbook. Therefore, this study is intended: (1) to describe whether the reading materials in English in Focus textbook published by Department of National Education for seventh graders of junior high school meet the aspect of contents suggested by Pusat Perbukuan, Ministry of National Education (2) to describe whether the reading materials in English in Focus textbook published by Department of National Education for seventh graders of junior high school meet the aspect of presentation suggested by Pusat Perbukuan, Ministry of National Education (3) to describe whether the reading materials in English in Focus textbook published by Department of National Education for seventh graders of junior high school meet the aspect of language use and readability suggested by Pusat Perbukuan, Ministry of National Education, and (4) to describe whether the reading materials in English in Focus textbook published by Department of National Education for seventh graders of junior high school meet the aspect of relation between chapter suggested by Pusat Perbukuan, Ministry of National Education. RESEARCH METHODOLOGY This study is concerned with analyzing the content of a textbook, in this case is the reading materials of an English textbook entitled “English in Focus for Grade VII Junior High School” published by Department of National Education, with the quality of English textbook (based on aspect of contents, aspect of presentation, aspect of language use and readability, also aspect of relation between chapters) suggested by Pusat Perbukuan, Department of National Education. Based on the objectives of the study, the design used in this study was descriptive qualitative. As stated by Ary et al (2010:29), “the goal of qualitative research is a holistic picture and depth of understanding rather than a numeric analysis of data”. The result of this study would be described in the form of words (qualitatively) without any statistical calculation. The object of this study was the English textbook for the seventh graders of junior high school entitled English in Focus. This book was written by Artono Wardiman et al. This textbook was known as one of the BSE (Buku Sekolah Elektronik) which was published by Department of National Education. There were two reasons of why the researcher wanted to analyze this textbook. Firstly, the textbook was recommended by Department of National Education and it was used in some public and private schools. Secondly, there was no previous study which analyzed the reading materials found in the textbook based on the aspect of contents, aspect of presentation, aspect of language use and readability, also aspect of relation between chapters. The data of this study was the reading materials which were found in “English in Focus” textbook in the first semester. This textbook consists of eight units and a hundred and seventy six pages. The first semester was discussed about chapter one to chapter four. The instrument which was used to analyze the data in this study is checklist. There were four checklists which were applied to answer the research questions. First, the checklist used to analyze the relevancy between reading materials found in the textbook with the aspect of contents. Second, the checklist used to analyze the relevancy between reading materials found in the textbook with the aspect of presentation. Third, the checklist used to analyze the relevancy between reading materials found in the textbook with the aspect of language use and readability. Fourth, the checklist used to analyze the relevancy between reading materials found in the textbook with the aspect of relation between chapters. The technique which was used in collecting the data is document analysis. First, the researcher collected the textbook entitled English in Focus for seventh graders of junior high school published by Department of National Education. Then, the researcher overviewed the contents of the textbook especially the reading materials. After that, the researcher selected checklists suggested by Pusat Perbukuan, Ministry of National Education. In this point, the researcher only choose some points which refer to the reading materials point of view. Last, the data of the textbook were collected by analyzing the reading materials based on the aspects of quality English textbook suggested by Pusat Perbukuan, Ministry of National Education. After collecting the data, analysis toward the data was needed. Data analysis was one of the ways which was used to analyze the data related with the research questions. There were several steps taken in analyzing the data: (1) Analyzing the reading materials based on the aspects of quality English textbook; (2) Describing the result of the findings to find out whether the textbook can meet the criteria of quality English textbook or not; (3) Concluding the result of the analysis in the form of words. RESULT AND DISCUSSION In this part, there will be presented results and discussion of the relevancy between reading materials with aspect of contents, aspect of presentation, aspect of language use and readability, also aspect of relation between chapters. The Relevancy between Reading Materials in English in Focus Textbook with Aspect of Contents Adapted from Ministry of National Education In this part, there will be The first research question is about the relevancy between reading materials in English in Focus textbook with aspect of contents adapted from Ministry of National Education. To answer this research question, the researcher should analyze six points according to the aspect of contents. In the first point, the researcher analyzed the conformity between reading materials and curriculum. Based on the result, the researcher found that most of reading materials were not in line with the 2006 English Standard Competence. It was because the reading materials such as announcement, greeting card, shopping list, SMS and instruction were not covered in the English in Focus textbook. While, in the second point, the researcher reviewed kind of genres found in the reading materials. The reading materials found in the textbook were compatible with the second point of aspect of contents. It is because the reading materials in the first semester consists of some genres. In the third point, the researcher reviewed the arrangement of reading materials based on the level of difficulty. Actually all the materials which were presented from the first to fourth chapter were varied and there were no repeated explanation. Therefore, the reading materials found in the textbook were compatible with the third point of aspect of contents. Meanwhile, in the fourth point, the researcher analyzed reading tasks which are given to develop students’ ability. All the reading tasks which were presented in each chapter were enough; it can be used for exercise in the class even for homework. Therefore, the reading materials found in the textbook were compatible with the fourth point of aspect of contents. In the fifth point, the researcher analyzed about the reading materials which are supporting life skills. Generally, each chapter of first semester in English in Focus textbook had already presented reading materials which were supporting students’ life skills. The differences between each chapter were the themes of the materials. All of those themes along with the exercises given had already presented life skills for the students. Therefore, the reading materials found in the textbook were compatible with the fifth point of aspect of contents. Furthermore, in the sixth point, the researcher analyzed the aspect of gender, religion, race and SARA. Based on the analysis, the materials presented in each chapter of first semester in English in Focus textbook had already compatible with the sixth point of aspect of contents. There was no emphasizing on the aspect of gender, ethnic, religion, race and SARA. The Relevancy between Reading Materials in English in Focus Textbook with Aspect of Presentation Adapted from Ministry of National Education The second research question is about the relevancy between reading materials in English in Focus textbook with aspect of presentation adapted from Ministry of National Education. To answer this research question, the researcher should analyze six points according to the aspect of presentation. In the first point of aspect of presentation, the researcher analyzed the learning objectives. Based on the presentation of each chapter in the textbook, the researcher found that the learning objectives which were stated in the first semester of English in Focus were compatible with the first point of aspect of presentation. There were explanation of learning objectives in each chapter which helped the students to understand about the materials that they were going to learn and ability that they got after learning the materials. Besides, the materials leaded the students to master the English communication competence. In the second point, the researcher reviewed about the presentation of each chapter in the textbook which should reflect the logical and coherence path. The researcher found that the first chapter to the fourth chapter already fulfilled the aspect of presentation which reflected the logical and coherence path. It was because each chapter presented the materials which were properly arranged and understandable. The third point was about the presentation of each chapter which arranged from easy to difficult materials. Based on the analysis result, the researcher found that all the reading materials were started from the easy part, then the level of difficulty were increased in the later materials. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the third point of aspect of presentation. Meanwhile, in the fourth point the researcher analyzed about the conformity between tasks and materials in the textbook. Based on the analysis result, the tasks and exercises given on the first to fourth chapters in English in Focus textbook were compatible with the reading materials given. Therefore, the reading materials presented in the first semester of English in Focus textbook were appropriate with the fourth point of aspect of presentation. In the fifth point, the researcher reviewed about the presentation of each chapter which engaging students to communicate using English actively. based on the analysis result, all the reading materials of the first semester of English in Focus textbook were presented both in texts and pictures, the materials were vary also. There were no repetition materials which made the students get bored. Because of that, the presentations of reading materials in each chapter were considered attractive. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the fifth point of aspect of presentation. In the sixth point, the researcher analyzed about the presentation of each chapter which encourages students to be interested in English subject. Based on the analysis result, all the materials presented in the first semester of English in Focus textbook were innovative since there were some exercises with different models and completed with some pictures in each chapter. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the sixth point of aspect of presentation. Furthermore, in the seventh point, the researcher analyzed about the presentation of each chapter which could encourages students to reflect and evaluate their self. Based on the analysis result, all materials in the first semester of English in Focus textbook were helped students to reflect and evaluate their self by providing some tasks and exercises in each chapter. From the breakdown tasks, it can be seen that each chapter of first semester in English in Focus textbook had already presented reading tasks which can be used to evaluate students’ comprehension. Kind of the reading tasks which were found were also innovative. It can make the students more motivated to do the tasks. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the seventh point of aspect of presentation. The Relevancy between Reading Materials in English in Focus Textbook with Aspect of Language Use and Readability Adapted from Ministry of National Education The third research question is about the relevancy between reading materials in English in Focus textbook with aspect of language use and readability adapted from Ministry of National Education. To answer this research question, the researcher should analyzed four points. In the first point, the researcher reviewed about the use of English language according to the English language rules. This point discuss about the use of punctuation. Based on the analysis result, the use of punctuations in the reading materials of first semester in English in Focus textbook were in good order. It was compatible with the English language rules. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the first point of aspect of language use and readability. Meanwhile, in the second point, the researcher analyzed about the use of English which is appropriate with needs of communication learning. It means that, the language which is used should be efficient and communicative so that students could understand the learning’s aim. Based on the analysis result, all the instructions given in the reading materials of first semester in English in Focus textbook were considered efficient and communicative. It was because the language which used was simple and brief so it was easy to understand by the students. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the second point of aspect of language use and readability. The third point is about the use of paragraphs which are presented effectively and efficiently by considering the aspect of coherence and cohesiveness. Based on the analysis result, there was no material in the form of paragraph in the first and fourth chapter of the textbook. But, the second and third chapter presented reading materials in the form of paragraph. Generally, texts which were presented in the second and third chapter had already fulfilled the rules of paragraph writing, which was consist of topic sentence, contents and closing sentence. The relations between concepts inside the paragraph were already appropriate too. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the third point of aspect of language use and readability. Furthermore, in the fourth point, the researcher analyzed the use of illustrations in the reading materials. Based on the analysis result, the researcher found that every chapter in the first semester of English in Focus textbook had presented some illustrations. All the illustrations given from the first to fourth chapter had already relevant with the topic of the material. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the fourth point of aspect of language use and readability. The Relevancy between Reading Materials in English in Focus Textbook with Aspect of Contents Adapted from Ministry of National Education The fourth research question is about the relevancy between reading materials in English in Focus textbook with aspect of relation between chapters adapted from Ministry of National Education. To answer this research question, the researcher should analyzed four points. In the first point, the researcher reviewed about the relevancy between materials with education purposes. Actually, the materials presented in the first semester of English in Focus textbook had appropriate with the education purposes (developing students’ awareness about the importance of learning English, developing students’ comprehension about the connection between languages and culture, so that they have cross cultural perception and engage their self to the culture diversity, also supporting the development of students’ intelligence in mastering knowledge, technology and arts). It means that the textbook did not only teach about the use of English, but also gave exercises which were supporting students’ intelligences. However, there was no material in the first semester of English in Focus which supported the development of technology and arts. Therefore, the reading materials presented in the first semester of English in Focus textbook were not compatible with the first point of aspect of relation between chapters. Meanwhile, in the second point, the researcher analyzed about the relevancy between the reading materials with the development of knowledge, technology and arts. Based on the analysis result, the material which could encourage the development of technology and arts had not been presented in the first semester of English in Focus textbook. But, all the materials given in the first semester were based on the aspect of human life, such as: introduction, things around us, life school and shopping. Therefore, the reading materials presented in the first semester of English in Focus textbook were not compatible with the second point of aspect of relation between chapters. The third point is about the relationship between materials in the textbook. Based on the analysis results, the reading material in the first chapter of English in Focus textbook were not related to another chapter on the textbook. While, the second, third and fourth chapter were related to each other and took advantages from the existing explanations in the previous chapter. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the third point of aspect of relation between chapters. Furthermore, in the fourth point, the researcher analyzed about anatomy, norms/ ethics and the completeness of a textbook. Based on the analysis, the researcher found that the English in Focus textbook had already presented the preface which was containing of vision and mission of the textbook. The preface can be found on page IV of the textbook. While, the guidance of the textbook had also already presented, it can be found on page V. The guidance consists of the explanation about each part of the textbook. Next, the textbook also presented table of contents, it can be found on page VI – VII. The tables of contents showed the distribution of four skills and its materials in each chapter. Further, the bibliography of the textbook had also already presented, it can be found on page 165. Last, the glossary can be found on page 167, in which this part contains definition of the words or foreign terms. Therefore, the reading materials presented in the first semester of English in Focus textbook were compatible with the four point of aspect of relation between chapters. It is because the textbook had already fulfilled the anatomy, norms and the completeness of a textbook. Overall, based on the analysis result of the four aspects, the researcher stated that the reading materials of first semester in the English in Focus textbook were not met the criteria of quality English textbook suggested by Pusat Perbukuan, Ministry of National Education. CONCLUSIONS AND SUGGESTIONS Conclusions This study aims to discover whether the reading material in English in Focus textbook could meet the aspects of a quality English textbook. The reading materials has been analyzed based on aspect of contents, aspect of presentation, aspect of language use and readability, also aspect of relation between chapters. Based on the aim, there are several conslusions that can be drawn. The first conclusion is regarding to the contents of the English in Focus textbook. Dealing with aspect of contents of the textbook, there are some points to analyze. Those points are the conformity between reading materials and curriculum, kind of genres found in the reading materials, the arrangement of reading materials based on the level of difficulty, reading tasks which are given to develop students’ abilty, the reading material which are supporting life skills and the reading materials which are consider about the aspects of gender, religion, race and SARA. Actually, all the points of aspect of contents had already fulfilled by English in Focus textbook, except the conformity between reading materials and curriculum. Based on the findings, there are some reading indicators that can not be found in the reading materials of first semester. While, the second conclusion is regarding to the presentation of English in Focus textbook. Dealing with the aspect of presentation of the textbook, there are some points to analyze. Those points are learning purpose which stated explicitly and lead to mastery of communication competence, the presentation of each chapter reflect the logical path and coherence, the presentation of each chapter arranged from easy to difficult materials, conformity between tasks and materials, the presentation of each chapter engaging students to communicate using English actively, the presentation of each chapter supporting students to be interested in English subject and the presentation of each chapter supporting students to reflect and evaluate their self. Based on the findings, all the points of aspect of presentation had already fulfilled by English in Focus textbook. The third conclusion is regarding to the language use and readability of English in Focus textbook. Dealing with the aspect of language use and readability of the textbook, there are some points to analyze. Those points are the standard of English language use according to the language rules, the use of English which is appropriate with needs of communication learning, the presentation of paragraphs which are presented effectively by considering coherences and cohesiveness and the use of illustrations which are functional and relevant with the materials. Based on the findings, all the points of aspect of language use and readability had already fulfilled by English in Focus textbook. Furthermore, the fourth conclusion is regarding to the relation between chapter of English in Focus textbook. Dealing with the aspect of relation between chapter of the textbook, there are some points to analyze. Those points are the relevancy between the materials with education purposes, the relevancy between the materials with the development of knowledge, technology and arts, the relationship between materials, and anatomy, norms/ ethics and the completeness of a textbook. Actually, all of the points of aspect of relation between chapter had already fulfilled by the textbook, except the relevancy between the materials with the development of knowledge, technology and arts. Based on the findings, the non-conformity found because there was no presentation about the development of technology and arts in the first semester of the textbook. In conclusion, it can be asserted that the reading materials presented in the first semester of English in Focus textbook were not meet the criteria of aspect of contents and aspect of relation between chapter suggested by Pusat Perbukuan, Ministry of National Education. Therefore, teacher should use an additional textbook as complement if they still want to use the English in Focus textbook Suggestions Dealing with the result of the study, some suggestions are given in this part. The suggestions are directed to the authors who compose and arrange the reading materials in the textbook entitled English in Focus, the teacher who have been or will be using the reading materials in the textbook and also the researchers who are interested in the same field of study . The suggestions are: 1. The authors who composed and arrange the reading material in English in Focus textbook; Because of some non-confomities found in the English in Focus textbook, the authors of the textbook should look at the 2006 English Standart Competence and criteria of quality English textbook suggested by Pusat Perbukuan, Ministry of National Education. This will give the reading materials in English in Focus textbook be more suitable both for the teacher who uses it as a tool in teaching and learning process and learners who use it as a guidance in learning. 2. The teachers who have been or will be using English in Focus textbook; The teacher who have been or will be using English in Focus textbook should be more selective in choosing English textbook. They have to be capable in analyzing textbook which will be used in English teaching and learning process. However, English in Focus textbook still can be used in the class, but teacher should use an additional textbook as complement to overcome the non-conformities of English in Focus textbook. 3. Other researchers; The future researchers can be conduct a research in the same field, for example by focusing on the presentation of other skills in the English in Focus textbook. It could be concerned with the listening, speaking or writing materials. REFERENCES Pusat Perbukuan.2005. Pedoman Penilaian Buku Pelajaran Bahasa Inggris untuk Sekolah Menengah Pertama dan Sekolah Menengah Atas. Departemen Pendidikan Nasional. Brown, Douglas. 2000. Teaching by Principles- 2nd Edition. Longman. Departemen Pendidikan Nasional. 2005. Pedoman Penulisan Buku Pelajaran-Penjelasan Standar Mutu Buku Pelajaran Bahasa Inggris. Nunan, David. 2005. Practical English Language Teaching Grammar. New York, NY: Mc Graw-Hill Companies, Inc. Nunan, David. 2003. Practical English Language. Singapore: Mc Graw Hill. Alyousef, Hesham Suleiman. 2005. Teaching Reading Comprehension to ESL/ EFL Learners.The Reading Matrix, Vol. 5 No. 2; 144. Harmer, Jeremy. 1998. How to Teach English. England: Longman. Budiharso, Teguh. 2004. Prinsip dan Strategi Pengajaran Bahasa. Surabaya: Lutfansah. Tomlinson, Brian. 1999. Materials Development in Language Teaching II. Cambridge: Cambridge University Press. Richard, Jack C. 2001. Curriculum Development in Language Teaching. Cambridge: Cambridge University Press. Gerry Abbott, John Greenwood, Douglass McKeating and Peter Wingard. 1981. The Teaching of English as an International Language. Collins: Glasgow and London. Mandasari, Yuyun Putri. 2007. An Analysis of the Reading Materials in Being Competent in English for the First Year Students of Senior High School Published by Mediatama. Unpublished Thesis: Universitas Negeri Surabaya Richards, Jack, C. 2001. Curriculum Development in Language Teaching. USA: Cambridge University Press. Carr, Judy, F, and Douglas E. Harris. 1993. Getting it Together (Process Workbook for K12 Curriculum Development, Implementation and Assesment. Massachusetts: Allyn and Bacon. Dubin, Fraida and Elite, Olsthain. 1986. Course Design: Developing Programs and Material for Language Learning. London: Cambridge University Press.